Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Team Game Tournament Terhadap Pemahaman Siswa Pada Mata Pelajaran Fiqih - Sulaiman, Husnan; Devi, Anisa (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Understanding is the ability to grasp the meaning and significance of the material studied. Currently, students' comprehension in the subject of Fiqh is low, as evidenced by test results showing that 47% of students have not met the Minimum Mastery Criteria (KKM). This deficiency may be attributed to the lack of variation in the teaching methods employed by educators during lessons. The cooperative learning model of the team game tournament type is a pedagogical approach that engages all student activities and integrates learning with play, thereby potentially increasing students' interest and comprehension. This study aims to describe the impact of the cooperative learning model, specifically the team game tournament type, on students' understanding of the Fiqh subject. The research method used is a quantitative experimental approach. Data collection techniques include observation, tests, and document analysis, while data processing employs statistical analysis. The findings indicate that the average score of the experimental group before the intervention was 72.8, which increased to 90.2 after the intervention. This is higher compared to the control group, which had an average score of 72.4 before and 81.1 after the intervention. The experimental group was taught using the cooperative learning model of the team game tournament type, while the control group was taught using the traditional lecture method. The t-test results show that the calculated t-value is 2.451, which is greater than the t-table value of 1.701 at a significance level of 0.05, leading to the acceptance of the alternative hypothesis (Ha). This indicates that there is a significant effect of the cooperative learning model of the team game tournament type on students' understanding in the subject of Fiqh. Keywords : Cooperative Learning Model, Team Game Tournament, Student Understanding, Fiqh Subject